Sorties scolaires dans les musées de sciences : étudier l’émancipation par l’analyse du sujet didactique - Cora Cohen-Azria (Recherches en Éducation)
This text is a contribution to thinking about emancipation functions and their conditions during academic visits in museums. From a didactical point of view, studying those situations leads us to analyse them through the notion of subject. Indeed, it comes to analyse together, on one hand, the didactic subject during singular situations like academic visits in museum, on an other hand, the institutional subject according to the reference institution involved in this partnership, finally the subject author of speeches (scientifical, museological or scholastic sciences). Although emancipation deals with an individual in relation to a group, academic visits in museum are, most of the time, based on a collective experience. Those are the dimensions elaborated in this article leading us to question about (de)personalization of the speeches producted by scientists, museologists and school-visitors.